H2 Kinetic Isotope Fractionation Superimposed by Equilibrium Isotope Fractionation During Hydrogenase Activity of D. vulgaris Strain Miyazaki - Löffler, Michaela; Kümmel, Steffen; Vogt, Carsten; Richnow, Hans-Hermann (Frontiers in Microbiology, 2019)
We determined 2H stable isotope fractionation at natural abundances associated with hydrogenase activity by whole cells of Desulfovibrio vulgaris strain Miyazaki F expressing a NiFe hydrogenase. Inhibition of sulfate reduction by molybdate inhibited the overall oxidation of hydrogen but still facilitated an equilibrium isotope exchange reaction with water. The theoretical equilibrium isotope exchange δ2H-values of the chemical exchange reaction were identical to the hydrogenase reaction, as confirmed using three isotopically different waters with isotope values of – 62, + 461 and + 1533 ‰. Expected kinetic isotope fractionation of hydrogen oxidation by non-inhibited cells was also superimposed by an equilibrium isotope exchange. The isotope effects were solely catalyzed biotically as hydrogen isotope signatures did not change in control experiments without cells of D. vulgaris Miyazaki.